Strategi Personal Branding Anies Baswedan dalam Membangun Komunikasi Politik Melalui Instagram - Kurniasih, Erni; Setianti, Yanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Individuals employ personal branding as a strategy to establish credibility and identity in the public sphere, particularly through social media platforms like Instagram. Anies Baswedan, an Indonesian politician, effectively leveraged social media, particularly Instagram, to bolster his personal branding and political communication. This study aims to scrutinize Anies Baswedan's personal branding strategy in shaping political communication via Instagram, emphasizing its distinctiveness, relevance, and content consistency. Employing a qualitative approach, data was collected through observation and content analysis of Anies Baswedan's Instagram account (@aniesbaswedan) from October 16, 2017, to Monday, May 15, 2022. Findings reveal that Anies Baswedan's personal branding on Instagram for political communication exhibits uniqueness, relevance, and consistency, pivotal elements of his branding strategy. His authenticity and everyday life aspects fostered a relatable atmosphere with followers, coupled with a rhetorical, relaxed, natural, and persuasive communication style. Content consistently addressed current issues, delivering leadership messages through diverse visual and narrative formats. Anies Baswedan's Instagram-based personal branding strategy effectively optimizes uniqueness, relevance, and consistency to enhance political communication and strengthen audience connections. Public figures and politicians can glean insights from Anies's Instagram personal branding strategy to enhance communication and audience engagement. This underscores the significance of personal branding in the realm of political communication on social media platforms such as Instagram.